Economic Feasibility of an In‐Pond Raceway System for Commercial Catfish Production in West Alabama. (6th January 2014) - Brown, Travis W.; Hanson, Terrill R.; Chappell, Jesse A.; Boyd, Claude E.; Wilson, Dean S.
Abstract: Our objective was to improve profitability of catfish farming by demonstrating methods to achieve high levels of survival, feed performance, and efficiency in a commercial farm setting. During 2007, a commercial‐scale in‐pond raceway system (IPRS) was constructed in a 6.0‐acre earthen pond on a catfish farm in west Alabama. The IPRS consisted of six raceways, each stocked with uniform‐sized Channel Catfish Ictalurus punctatus or hybrid catfish (Channel Catfish × Blue Catfish I. furcatus ). Co‐cultured fish species (Paddlefish Polyodon spathula and Nile Tilapia Oreochromis niloticus ) were stocked and harvested in the outside area of the pond containing the IPRS. Results from the 2008 production season were used to project 12 months of production from stocking either Channel Catfish or hybrid catfish in the IPRS. In addition, Channel Catfish production in traditional ponds was monitored from 2005 to 2009 on the same farm (∼430 water‐acres). The 8‐month IPRS results were compared with (1) the 12‐month average production from the traditional farm and (2) the 12‐month projected production in the IPRS. Variable and fixed costs to produce catfish were US0.71 and 0.14 per pound, respectively, in the IPRS during the 8‐month study; 0.78 and 0.05 per pound for the 12‐month average performance of the traditional farm; 0.74 and 0.19 per pound for 12‐month projected Channel Catfish production; and 0.64 and 0.11 per pound for 12‐month projected hybrid catfish production. Income above variable costs and net returns to land from using the IPRS increased when co‐cultured species were included in the economic analysis. Our results showed that the IPRS can be efficient at producing catfish and co‐cultured species, although the energy input per pound was greater than that for the traditional farm. Additional studies using the IPRS for fish production are underway to verify our initial research results.